Comparison of The Canary System and DIAGNOdent for the in vitro detection of caries under opaque dental sealants. Issue 4 (26th September 2016) - Silvertown, Josh D.; Wong, Bonny P. Y.; Abrams, Stephen H.; Sivagurunathan, Koneswaran S.; Mathews, Sapna M.; Amaechi, Bennett T.
Abstract: Aim: The aim of the present study was to investigate the ability of operators using The Canary System and DIAGNOdent to detect natural pit and fissure caries under four commonly‐used opaque dental sealants. Methods: Mixed sound and carious pits/fissures (N = 105) selected from 40 human teeth were randomly assigned (10 teeth/group) to one of four opaque sealant groups (Delton, Embrace WetBond, Helioseal F, UltraSeal XT Plus). Selected pits/fissures sites on occlusal surfaces were scanned with The Canary System and DIAGNOdent, sealed, re‐scanned, and subjected to polarized light microscopy to confirm whether the scanned regions were sound or carious. Sensitivities and specificities for each detection method before and after sealant placement were calculated. Results: The Canary System and DIAGNOdent were able to distinguish between sound and carious tissue beneath opaque sealants with an accuracy of 76% and 59%, respectively. Conclusions: The Canary System can serve as a clinical tool to aid dental professionals to detect and monitor the status of caries lesions and tooth structure underneath sealant. The increased likelihood of false‐positive diagnoses with DIAGNOdent due to intrinsic auto‐fluorescence of sealant filler and opacifying agents might limit its usefulness as an aid to detect caries underneath opaque sealants.